(untitled) (Jurnal Ilmiah Metansi (Manajemen dan Akuntansi), 2024)
Organisational culture is formed by leaders and applied to subordinates. Culture also changes according to the environment and the needs of the organisation. In the Public Housing and Settlement Area Office of North Nias Regency in carrying out their duties and responsibilities. In the Office of Public Housing and Settlement Areas of North Nias Regency, in carrying out their duties and responsibilities, it is not in accordance with what is expected that performance where the problem is that employees in the agency still unable to carry out and complete their duties properly. The purpose of the study was to determine the Organisational Culture and to determine Employee Performance at the Public Housing and Settlement Area Office of North Nias Regency. In research using qualitative methods using data and information using observation, documentation and interviews. The result of this research is that the importance of a strong organisational culture lies in its ability to create commitment to improving the quality of housing and settlements, effective and efficient resource management, and adaptation to changing times, technology, regulations, and community needs. By applying these values, the Public Housing and Settlement Areas Office can become an effective, responsive, and trusted institution by the community in delivering housing programmes and maintaining integrity. In employee performance, the need for efficiency includes the ability to plan and manage housing programmes within budget and time, effectiveness involves resource management and internal communication, innovation is needed to face development challenges, and responsibility to the community is a determining factor for performance.